ANALYSIS OF PARADIGM OF EDUCATION IN THE MODERN EDUCATION SYSTEM - Bigar, H.P. (Pedagogy of Higher and Secondary Education, 2022)
Shaping a person as personalities requires from the society of constant and conciously organizined improvements of public education system. Such practice of transformation of the established forms of unbringing impossible without full tilts on scientifically - theoretical psy chological knowledge of regularities of development of child. Essence really humanistic rela tions to unbringing a child denominated in the thesis of its activity as enjoying full rights, rather then object of process of education. Consequently, it is important so build a pedagogi cal process to managed child activity, organizining its active by completion of independent and responsible actions The Teacher can and obliged to help a grow person to pass this - always unique and independent- a way morally and social development Education presents itself not adjustment a children, teenagers, to available forms sociality, not tailoring under the certain standard.